2013
DOI: 10.1108/13639511311329714
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a police organizational model for crime reduction

Abstract: PurposeThis paper aims to present the evaluation results of a practice‐based research partnership to develop and implement a new police organizational model for crime reduction into one police agency which was implemented based on the best practices of problem‐oriented policing, hot spots policing, and Compstat.Design/methodology/approachA qualitative process evaluation of organizational changes and an impact evaluation examining specific crime types was conducted over seven years to determine increased effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…While crime analysis does not replace the work and skills of sworn police personnel, it is designed to complement and add value to that work (Santos & Taylor, 2014, p. 502). Indeed, Santos (2013a) found that the implementation of the stratified model of problem solving, analysis, and accountability, which incorporates rigorous crime analysis in the daily functions of all levels of a police agency, was associated with significant crime reductions in Port St. Lucie, FL. 2 Crime analysis is widely recognized as involving five primary functions: intelligence analysis, criminal investigative analysis, tactical analysis, strategic analysis, and administrative analysis (Boba, 2001(Boba, , 2009Bruce, 2008;Santos, 2013b).…”
Section: Crime Analysts As a Vehicle For In-house Program Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While crime analysis does not replace the work and skills of sworn police personnel, it is designed to complement and add value to that work (Santos & Taylor, 2014, p. 502). Indeed, Santos (2013a) found that the implementation of the stratified model of problem solving, analysis, and accountability, which incorporates rigorous crime analysis in the daily functions of all levels of a police agency, was associated with significant crime reductions in Port St. Lucie, FL. 2 Crime analysis is widely recognized as involving five primary functions: intelligence analysis, criminal investigative analysis, tactical analysis, strategic analysis, and administrative analysis (Boba, 2001(Boba, , 2009Bruce, 2008;Santos, 2013b).…”
Section: Crime Analysts As a Vehicle For In-house Program Evaluationsmentioning
confidence: 99%
“…While crime analysis does not replace the work and skills of sworn police personnel, it is designed to complement and add value to that work (Santos & Taylor, 2014, p. 502). Indeed, Santos (2013a) found that the implementation of the stratified model of problem solving, analysis, and accountability, which incorporates rigorous crime analysis in the daily functions of all levels of a police agency, was associated with significant crime reductions in Port St. Lucie, FL. 2…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…First, implementation is an integral part of the policy process, necessary for linking policy outputs with outcomes (Maguire, 2009 1984). Second, even under the best of circumstances, policy implementation is an intricate and eminently demanding process (e.g., Santos, 2013). This complexity is reflected in a two-dimensional analytical framework that acknowledges the relevance of both dosage, or the "intensity with which a policy is implemented," and fidelity, or "the extent to which a reform, as implemented, matches the way it was originally conceived or envisioned" (Maguire, Uchida, & Hassell, 2010, p. 1).…”
Section: Policy Implementationmentioning
confidence: 99%
“…In fact, these officers receive policy and managerial guidance through the chain of command, where first line supervisors are the most direct, most influential voices of accountability (Kelling & Bratton, 1993). The presence of strong, supportive leadership that places a high priority on the implementation process has also been shown to be critical to overall success (Fernandez & Rainey, 2006;Santos, 2013). Leaders who are vocally committed to the implementation process and skilled in developing and communicating organizational agendas and priorities are particularly valuable (Bingham & Wise, 1996).…”
Section: Policy Implementationmentioning
confidence: 99%
“…Crime analysis is the study of crime data and other related information to assist law enforcement in reducing or preventing crime, apprehending criminals, and evaluating departmental policies. Crime analysis has been related to lower rates of crime, more effective policing policies, and increased efficiency in resource allocation, particularly in departments which utilize crime analysis when making decisions (Baltaci, 2010;Santos, 2012;Santos 2014;Veigas & Lum, 2013). Crime analysts compile and analyze information on criminal activity, police response, and department policies reporting results to central command staff, area commanders, and patrol officers.…”
Section: Introductionmentioning
confidence: 99%